The shadow effect : illuminating the hidden power of your true self - Chopra, Deepak (HarperOne, 2010)
"The shadow is a part of the unconscious mind consisting of repressed weaknesses and base instincts. "Everyone carries a shadow," Jung wrote, "and the less it is embodied in the individual's conscious life, the blacker and denser it is." Now today's most popular spiritual teachers, Debbie Ford, Marianne Williamson, and Deepak Chopra join forces in this remarkable exploration of the dark side--the emotions and traits we are most afraid of and instinctively hide. When we reject or refuse to acknowledge this part of our nature we become susceptible to those emotions and traits negatively impacting us. The truth is the shadow makes it presence known whether we want it to or not. The difference is that if uninvited our dark side has the potential to hurt us and our loved ones at any moment. However by embracing our shadow we embark on an incredible, rewarding journey. This journey to wholeness, far from frightening, is empowering. By uncovering who we really are, the totality of our being, we access hidden strengths, boundless courage, and a clear path to happiness. Following a joint introduction, the book will be divided into three sections. Debbie will write on the personal shadow, Marianne will write about spirituality and our shadow, and Deepak will close with the collective shadow"--Provided by publisher.